2019
DOI: 10.1136/medethics-2019-105832
|View full text |Cite
|
Sign up to set email alerts
|

‘Serious’ factor—a relevant starting point for further debate: a response

Abstract: In this reply, we wish to defend our original position and address several of the points raised by two excellent responses. The first response (De Miguel Beriain) questions the relevance of the notion of ‘serious’ within the context of human germline genome modification (HGGM). We argue that the ‘serious’ factor is relevant and that there is a need for medical and social lenses to delineate the limits of acceptability and initial permissible applications of HGGM. In this way, ‘serious’ acts as a starting point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In their 2020 Report, the International Commission on the Clinical Use of Human Germline Genome Editing concluded that i-HGE should be limited to serious monogenic diseases and to ‘changing a pathogenic genetic variant … to a sequence that is common in the relevant population and that is known not to be disease-causing’ (National Academy of Medicine et al 2020 , p. 3 [recommendation 4.2]). Erika Kleiderman and colleagues likewise stated that the ‘seriousness’ of a condition is relevant to decision-making regarding the use of i-HGE, as a greater benefit could offset the risks associated with a previously untested procedure (Kleiderman, Ravitsky, and Knoppers 2019 ; 2020 ). The authors further derive the significance of seriousness from a human rights-based framework, specifically in the ‘right to science’ and the ‘right to the highest attainable health’, to bridge the divide between objective and subjective definitions of health (Kleiderman, Ravitsky, and Knoppers 2019 ; 2020 ).…”
Section: Mapping a Responsible Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In their 2020 Report, the International Commission on the Clinical Use of Human Germline Genome Editing concluded that i-HGE should be limited to serious monogenic diseases and to ‘changing a pathogenic genetic variant … to a sequence that is common in the relevant population and that is known not to be disease-causing’ (National Academy of Medicine et al 2020 , p. 3 [recommendation 4.2]). Erika Kleiderman and colleagues likewise stated that the ‘seriousness’ of a condition is relevant to decision-making regarding the use of i-HGE, as a greater benefit could offset the risks associated with a previously untested procedure (Kleiderman, Ravitsky, and Knoppers 2019 ; 2020 ). The authors further derive the significance of seriousness from a human rights-based framework, specifically in the ‘right to science’ and the ‘right to the highest attainable health’, to bridge the divide between objective and subjective definitions of health (Kleiderman, Ravitsky, and Knoppers 2019 ; 2020 ).…”
Section: Mapping a Responsible Pathwaymentioning
confidence: 99%
“…Erika Kleiderman and colleagues likewise stated that the ‘seriousness’ of a condition is relevant to decision-making regarding the use of i-HGE, as a greater benefit could offset the risks associated with a previously untested procedure (Kleiderman, Ravitsky, and Knoppers 2019 ; 2020 ). The authors further derive the significance of seriousness from a human rights-based framework, specifically in the ‘right to science’ and the ‘right to the highest attainable health’, to bridge the divide between objective and subjective definitions of health (Kleiderman, Ravitsky, and Knoppers 2019 ; 2020 ).…”
Section: Mapping a Responsible Pathwaymentioning
confidence: 99%